The effects of different ensiling methods on the silage quality made with whole-crop barley at boot stage - Çerçi, I. Halil; Şahin, Kazım; Güler, Talat; Çelik, Sait (Scientific and Technical Research Council of Turkey, 1996)
In this study, whole-crop barley planted in Autumn-winter as second crop for giving an opportunity planting of main crop was harvested at boot stage at the begining of spring. Barley was chopped into 1.5-2 cm pieces and divided into groups as follows: Y (unwilled) group, ensiled as fresh on harvest day, P (wilted) group, ensiled after wilting 24 h, Y+S (unwilted material 87% + Straw 13%) group, ensiled after harvest without wilting and added straw with treated HCl. The changes in nutrients cotent of silages and in vitro digestibility of dry matter were investigated. Dry matter, crude protein, eter extract, crude fiber and acid detergent fiber contents increased graeter in silage groups as compared in fresh materials. However, nitrogen free extract and neutral detergent fiber contents decreased. Dry matter and nitrogen free extract contents were not different in P and Y+S groups, but the lowest values were determined in Y group (P<0.01). While the highest crude fiber, acid detergent fiber contents were determined in Y+S. this group followed by Y and P groups (P<0.01). Crude protein and ether extract contents were less in Y+S group than in other groups. Total acid, lactic acid, acetic add contatrations were higher in Y+S group than Y and P groups. The lowest pH was found in Y+S group. On the other hand, the highest ammonia-N and butyric acid concentratios were determined in Y group. The in vitro digestibilly of dry matter was not significantly altered (P>0.05) in fresh material. The in vitro digestibility of dry malter of silages was determined 60.63, 64.32 and 62.24% in Y, P and Y+S groups, respectively. The differences were statistically significant between groups (P<0.01).
Körpe Arpa Hasili ile Yapilan Silajlarda Farkli Silolama Yöntemlerinin Silaj Kalitesine Etkileri
Keywords: Digestibility; Second crop; Silage quality; Whole-crop barley